High-entropy carbide composite material with friction-induced self-lubricating function

CN122977847APending Publication Date: 2026-10-27LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611163787.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]但目前尚无碳纳米管与高熵碳化物反应制备高性能自润滑高熵复合材料的任何报道

Benefits of technology

1、本发明利用碳纳米管作为碳源,通过调控碳纳米管添加量、反应温度和时间,可精确控制碳纳米管衍生润滑相的含量和结构保留程度。较低的温度或较短的保温时间可保留更多碳纳米管结构,形成富润滑相复合材料;而较高的温度或较长的保温时间则促进碳纳米管向石墨化碳转变,获得不同形式的碳润滑相。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977847A_ABST
    Figure CN122977847A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of high-entropy carbide composite material with friction-induced self-lubricating function, which is composed of high-entropy carbide matrix and carbon nanotube derived lubricating phase;The chemical formula of the high-entropy carbide matrix is (A1A2A3A4A5)C, with face-centered cubic crystal structure, wherein A1, A2, A3, A4, A5 are any five elements in W, Zr, Nb, Hf, Ta, Ti, Mo, and wherein A1, A2, A3, wherein A1, A2, A3, A4, A5 and C are in a molar ratio of 1:1:1:1:1:5.The present application can form uniformly distributed carbon nanotube derived lubricating phase, and the prepared high-entropy carbide composite material has high hardness and excellent self-lubricating performance, which can effectively solve the problem of water-cooled wall surface coking and contamination in high-alkali coal combustion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-entropy ceramic materials and self-lubricating composite materials, and particularly to a high-entropy carbide composite material with friction-induced self-lubricating function. Background Technology

[0002] High-entropy carbides are single-phase rock-salt structure ceramics formed by the solid solution of four or more transition metal carbides in equimolar or near-equimolar proportions. Their core characteristics lie in the thermodynamic stabilization effect driven by high configurational entropy, lattice distortion effect, and slow diffusion effect. Compared to single carbides, high-entropy carbides exhibit excellent high-temperature stability, high hardness, high wear resistance, and good oxidation resistance due to the disordered occupation of multiple metal atoms, leading to significant lattice distortion and local electronic state reconstruction. They show broad application prospects in aerospace thermal protection, key components of hypersonic vehicles, and high-temperature structural materials.

[0003] However, as modern industrial equipment develops towards higher parameters, the friction and wear problems of moving parts under harsh conditions such as high temperature and heavy load are becoming increasingly prominent. Although traditional high-entropy carbide ceramics have high hardness and good wear resistance, their intrinsic coefficient of friction is usually high, and they are prone to severe adhesive wear and oxidative wear under high temperature and unlubricated conditions, making it difficult to meet the service requirements of long service life and low energy consumption. Therefore, how to endow high-entropy carbides with good self-lubricating properties has become a key scientific problem that urgently needs to be solved in this field.

[0004] Carbon nanotubes, as a novel carbon material, possess a unique tubular structure, excellent mechanical properties, and self-lubricating characteristics. Studies have shown that carbon nanotubes, as a lubricating phase additive, can significantly reduce the coefficient of friction in materials. They can form a transfer film during friction, and the rolling effect of carbon nanotubes also helps reduce friction. However, traditional methods of introducing carbon nanotubes as an excipient phase into ceramic matrices often encounter problems such as uneven dispersion, weak interfacial bonding, and poor high-temperature stability, limiting their lubricating effect.

[0005] Joule heating is an emerging material preparation method that utilizes electric current to directly heat samples, achieving ultra-rapid heating (up to 1000℃ / s and above) and short-term holding time. This technology offers advantages such as rapid heating, short reaction time, and low energy consumption, effectively suppressing grain growth and element volatilization, making it particularly suitable for the rapid synthesis of high-entropy materials. Simultaneously, the ultra-fast heating process helps preserve the original structure of carbon nanotubes, avoiding structural damage caused by prolonged high-temperature treatment.

[0006] However, there are currently no reports on the preparation of high-performance self-lubricating high-entropy composite materials by reacting carbon nanotubes with high-entropy carbides. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a high-entropy carbide composite material with good performance and friction-induced self-lubricating function.

[0008] To address the aforementioned problems, the present invention provides a high-entropy carbide composite material with friction-induced self-lubricating function, characterized in that: the composite material is composed of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase; the high-entropy carbide matrix has the chemical formula (A1A2A3A4A5)C and has a face-centered cubic crystal structure, wherein A1, A2, A3, A4, and A5 are any five elements selected from W, Zr, Nb, Hf, Ta, Ti, and Mo, and the molar ratio of A1, A2, A3, A4, and A5 to C is 1:1:1:1:1:5.

[0009] The mass ratio of the carbon nanotube-derived lubricating phase to the high-entropy carbide matrix is ​​0.01~0.15:1.

[0010] The coefficient of friction of the composite material is 0.1 to 0.45 in the temperature range of room temperature to 1000°C.

[0011] The preparation method of a high-entropy carbide composite material with friction-induced self-lubricating function as described above is characterized by: firstly, using carbon nanotubes as the carbon source, and five metal oxides selected from WO3, Nb2O5, HfO2, ZrO2, Ta2O5, TiO2, and MoO3 as raw materials, weighing the metal oxides according to the equimolar ratio of the metal elements, and weighing the carbon nanotubes according to the molar ratio of carbon in the carbon nanotubes to each metal element of 5:1; then, mixing the metal oxides and carbon nanotubes, and placing them in a high-energy ball mill for wet ball milling to obtain a mixed slurry; after drying the mixed slurry, a composite precursor powder is obtained; finally, the composite precursor powder is placed in a Joule heating rapid heating device and subjected to a Joule heating rapid carbothermic reduction reaction under a protective atmosphere; after the reaction is completed, cooling is performed to obtain a powdered high-entropy carbide composite material with friction-induced self-lubricating function.

[0012] The purity of the metal oxides is not less than 99.95%, and the particle size is not less than 100 mesh.

[0013] The carbon nanotubes are multi-walled or single-walled carbon nanotubes with a purity of not less than 95%, a diameter of 5~50nm, and a length of 1~20μm.

[0014] The ball milling conditions are as follows: rotation speed of 200~400 rpm, ball-to-material mass ratio of 5:1~15:1, ball milling time of 5~15 h, solvent of anhydrous ethanol, and mass ratio of anhydrous ethanol to raw material of (1~3):1.

[0015] The drying conditions refer to a temperature of 60~85℃ and a time of 12~24h.

[0016] The Joule heating rapid heating device is a Joule heating reactor, with argon or nitrogen as the protective atmosphere and a gas flow rate of 0.1~1L / min; the heating rate is 100~600℃ / s, the heating temperature is 2000~2300℃, and the holding time is 30~180s.

[0017] The powdered high-entropy carbide composite material with friction-induced self-lubricating function is formed into a bulk material by spark plasma sintering or hot pressing sintering. The sintering temperature is 1800~2000℃, the pressure is 30~50MPa, the holding time is 5~15min, and the relative density after sintering is not less than 98%, and the Vickers hardness is not less than 17GPa.

[0018] Compared with the prior art, the present invention has the following advantages: 1. This invention utilizes carbon nanotubes as a carbon source. By adjusting the amount of carbon nanotubes added, the reaction temperature, and the time, the content and structural retention of the carbon nanotube-derived lubricating phase can be precisely controlled. Lower temperatures or shorter holding times can retain more carbon nanotube structures, forming a lubricating phase-rich composite material; while higher temperatures or longer holding times promote the transformation of carbon nanotubes into graphitized carbon, obtaining different forms of carbon lubricating phases.

[0019] 2. In this invention, carbon nanotubes not only provide carbon elements to generate high-entropy carbides during the reaction process, but also allow some carbon nanotube structures to be retained or transformed into graphitized carbon by controlling the reaction conditions, forming a uniformly distributed carbon nanotube-derived lubricating phase.

[0020] 3. This invention utilizes the advantage of rapid Joule heating to complete the reaction in a very short time, effectively preserving the lubricating structure of carbon nanotubes, while achieving uniform dispersion of carbon nanotubes in the matrix, providing a new technical approach for developing high-performance self-lubricating high-entropy ceramics.

[0021] 4. The high-entropy carbide composite material prepared by this invention possesses both high hardness and excellent self-lubricating properties. The carbon nanotube-derived lubricating phase easily forms a transfer film on the contact surface during friction, and its tubular structure can also generate a rolling effect, significantly reducing the coefficient of friction. At the same time, the multi-metal elements in the high-entropy carbide matrix can undergo tribochemical reactions under the action of frictional heat, and work synergistically with the carbon lubricating film to achieve wide-temperature-range self-lubrication.

[0022] 5. The high-entropy carbide composite material prepared by this invention can effectively solve the problems of coking and contamination on the surface of water-cooled walls during the combustion of high-alkali coal, and achieve high-temperature lubrication and self-stripping functions.

[0023] 6. The preparation method of this invention is simple, the reaction is rapid, and the energy consumption is low, making it suitable for large-scale production. The resulting composite material is in powder form and can be further processed into bulk materials, offering flexible applications. Attached Figure Description

[0024] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0025] Figure 1 The image shows the XRD pattern of the composite material obtained in Example 1 of this invention.

[0026] Figure 2 This is the friction coefficient curve of the composite material obtained in Example 2 of the present invention.

[0027] Figure 3 These are scanning electron microscope (SEM) images of the composite material obtained in Example 3 of this invention at different magnifications. The left image shows 20 μm, and the right image shows 10 μm. Detailed Implementation

[0028] A high-entropy carbide composite material with friction-induced self-lubricating function is disclosed. This composite material consists of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase. The high-entropy carbide matrix has the chemical formula (A1A2A3A4A5)C and a face-centered cubic crystal structure, wherein A1, A2, A3, A4, and A5 are any five elements selected from W, Zr, Nb, Hf, Ta, Ti, and Mo, and the molar ratio of A1, A2, A3, A4, and A5 to C is 1:1:1:1:1:5. The carbon nanotube-derived lubricating phase originates from the carbon nanotubes used as the carbon source during the preparation process. After a rapid Joule-thermal carbothermal reduction reaction, some of the carbon nanotube structures are retained or transformed into graphitized carbon, which is uniformly distributed in the high-entropy carbide matrix, serving as the lubricating phase for friction-induced self-lubrication.

[0029] The mass ratio (g / g) of the carbon nanotube-derived lubricating phase to the high-entropy carbide matrix is ​​0.01~0.15:1.

[0030] The coefficient of friction of this composite material is 0.1~0.45 in the temperature range of room temperature to 1000℃.

[0031] A method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function: First, carbon nanotubes were used as the carbon source, and five metal oxides from WO3, Nb2O5, HfO2, ZrO2, Ta2O5, TiO2, and MoO3 were used as raw materials. The metal oxides were weighed according to the equimolar ratio of the metal elements, and the carbon nanotubes were weighed according to the molar ratio of carbon to each metal element of 5:1. Then, the metal oxides and carbon nanotubes were mixed and placed in a high-energy ball mill for wet ball milling at a speed of 200~400 rpm, a ball-to-material mass ratio (g / g) of 5:1~15:1, a ball milling time of 5~15 h, and anhydrous ethanol as the solvent, with an anhydrous ethanol to raw material mass ratio (g / g) of (1~3):1. After ball milling, a mixed slurry is obtained. This slurry is dried at 60–85°C for 12–24 hours to obtain the composite precursor powder. Finally, the composite precursor powder is wrapped in carbon paper or carbon felt and placed in a Joule-thermal rapid heating device. Under a protective atmosphere, a Joule-thermal rapid carbothermal reduction reaction is carried out, causing the metal oxide to react with the carbon in the carbon nanotubes to generate high-entropy carbides. Simultaneously, some carbon nanotube structures are retained or transformed into graphitized carbon, forming a uniformly distributed carbon nanotube-derived lubricating phase. The Joule-thermal rapid heating device is a Joule-thermal reactor, with an argon or nitrogen protective atmosphere at a flow rate of 0.1–1 L / min; a heating rate of 100–600°C / s; a heating temperature of 2000–2300°C; and a holding time of 30–180 s. After the reaction is completed and cooled, a powdered high-entropy carbide composite material with friction-induced self-lubricating function is obtained.

[0032] Powdered high-entropy carbide composite materials with friction-induced self-lubricating function can also be made into bulk materials by spark plasma sintering or hot pressing sintering. The sintering temperature is 1800~2000℃, the pressure is 30~50MPa, the holding time is 5~15min, the relative density after sintering is not less than 98%, and the Vickers hardness is not less than 17GPa.

[0033] Among them, the purity of the metal oxides is not less than 99.95%, and the particle size is not less than 100 mesh.

[0034] The carbon nanotubes are multi-walled or single-walled carbon nanotubes with a purity of not less than 95%, a diameter of 5~50 nm, and a length of 1~20 μm.

[0035] Example 1 A high-entropy carbide composite material with friction-induced self-lubricating function is disclosed. The composite material consists of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase. The high-entropy carbide matrix is ​​composed of five metallic elements: Hf, Mo, Nb, Ta, and Ti. The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 20 nm, a length of 2 μm, and a carbon content of 95%.

[0036] Its preparation method: First, calculate the required mass of oxides based on the equimolar ratio of the metal elements, setting the amount of each of the five metal elements to 0.001 mol. Based on the molecular weight and number of metal atoms of each oxide, weigh out 0.2105 g of HfO2, 0.1439 g of MoO3, 0.1329 g of Nb2O5, 0.2209 g of Ta2O5, and 0.0799 g of TiO2. The total amount of metal elements is 0.005 mol. Assuming a carbon-to-metal molar ratio of 1:1, the required amount of carbon is 0.005 mol. Since the atomic weight of carbon is 12.01, the required mass of carbon is 0.0601 g. Weigh out 0.0626 g of carbon nanotubes.

[0037] The five metal oxides and carbon nanotubes weighed above were then placed together in the grinding jar of a high-energy ball mill for wet ball milling. Zirconia grinding balls were added at a ball-to-material mass ratio (g / g) of 8:1, and anhydrous ethanol was added as the grinding medium. The mass ratio of anhydrous ethanol to the total raw material mass (g / g) was controlled at 2.5:1. The ball mill speed was set to 250 rpm, and the milling was carried out for 15 hours, with a 5-minute pause every 30 minutes to prevent overheating of the system. After the ball milling was completed, a uniform slurry was obtained. The slurry was dried at 65℃ for 24 hours to allow the anhydrous ethanol to completely evaporate, thus obtaining the composite precursor powder.

[0038] Finally, the composite precursor powder was wrapped in carbon paper and placed in the reaction chamber of a Joule heating rapid heating apparatus. Argon gas was introduced as a protective atmosphere, with the gas flow rate controlled at 0.2 L / min. The heating program was set as follows: heating rate of 300 °C / s, target temperature of 2000 °C, and holding at the target temperature for 180 s. After the holding period, the mixture was allowed to cool naturally to room temperature, thus obtaining a powdered high-entropy carbide composite material with friction-induced self-lubricating function.

[0039] The obtained composite powder was subjected to phase analysis and structural characterization. Figure 1 The XRD diffraction pattern of the high-entropy carbide composite material shows a typical high-entropy carbide structure. It also shows that the main crystalline phase is a face-centered cubic high-entropy carbide with no obvious impurity peaks.

[0040] Example 2 A high-entropy carbide composite material with friction-induced self-lubricating function is disclosed. The composite material consists of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase. The high-entropy carbide matrix is ​​composed of five metallic elements: Zr, Nb, Hf, Ta, and Ti. The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10-20 nm, a length of 5-15 μm, and a carbon content of 97%.

[0041] Its preparation method: First, based on the required mass of oxides according to the equimolar ratio of the metal elements, the amount of each of the five metal elements is set to 0.001 mol. According to the molecular weight and number of metal atoms of each oxide, 0.1232 g of ZrO2, 0.1329 g of Nb2O5, 0.2105 g of HfO2, 0.2209 g of Ta2O5, and 0.0799 g of TiO2 are needed. The total amount of metal elements is 0.005 mol. Based on a carbon-to-metal molar ratio of 1:1, 0.0601 g of carbon is required, so 0.0620 g of carbon nanotubes are weighed.

[0042] The aforementioned metal oxide and carbon nanotubes were then placed in the ball mill jar of a high-energy ball mill for wet ball milling. Zirconia grinding balls were added at a ball-to-material mass ratio (g / g) of 12:1, and anhydrous ethanol was added at a mass ratio (g / g) of 2:1. The mixture was ball-milled at 300 rpm for 12 hours. After ball milling, a mixed slurry was obtained. The mixed slurry was dried at 75°C for 20 hours to obtain the composite precursor powder.

[0043] Finally, the composite precursor powder was wrapped in carbon felt and placed in a Joule thermal reactor under an argon atmosphere at a flow rate of 0.3 L / min. A rapid Joule thermal carbothermic reduction reaction was carried out by heating to 2100 °C at a rate of 400 °C / s and holding at that temperature for 120 s. After the reaction was completed, the mixture was cooled to obtain a powdered high-entropy carbide composite material with friction-induced self-lubricating function.

[0044] The obtained composite material was subjected to friction performance testing. The friction test was carried out using a reciprocating friction testing machine, with a fixed normal load of 3N, a reciprocating frequency of 5 Hz and a single stroke of 4 mm, and the overall test duration was controlled within 30 minutes. Real-time data of the friction coefficient were collected simultaneously during the test. The results are as follows: Figure 2 The results show that the composite material has a coefficient of friction of 0.27 at room temperature, exhibiting good self-lubricating properties.

[0045] Example 3 A high-entropy carbide composite material with friction-induced self-lubricating function is disclosed. The composite material consists of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase. The high-entropy carbide matrix is ​​composed of five metallic elements: Hf, Mo, Nb, Ta, and Ti. The carbon nanotubes are single-walled carbon nanotubes with a diameter of 1–3 nm, a length of 5–20 μm, and a carbon content of 92%.

[0046] Its preparation method: First, calculate the required mass of oxides based on the equimolar ratio of the metal elements, setting the amount of each of the five metal elements to 0.001 mol. Based on the molecular weight and number of metal atoms of each oxide, weigh out 0.2105 g of HfO2, 0.1439 g of MoO3, 0.1329 g of Nb2O5, 0.2209 g of Ta2O5, and 0.0799 g of TiO2. The total amount of metal elements is 0.005 mol. Based on a carbon-to-metal molar ratio of 1:1, the required mass of carbon is 0.0601 g, which translates to 0.0653 g of single-walled carbon nanotubes.

[0047] The metal oxide and single-walled carbon nanotubes were then mixed and placed in the ball mill jar of a high-energy ball mill for wet ball milling. Zirconia grinding balls were added at a ball-to-material mass ratio (g / g) of 10:1, and anhydrous ethanol was added at a mass ratio (g / g) of 1.5:1. The mixture was ball-milled at 350 rpm for 8 hours. After ball milling, a mixed slurry was obtained. The mixed slurry was dried at 80℃ for 15 hours to obtain the composite precursor powder.

[0048] Finally, the composite precursor powder was wrapped in carbon paper and placed in a Joule thermal reactor under an argon atmosphere at a flow rate of 0.4 L / min. The temperature was increased to 2300 °C at a rate of 500 °C / s and held for 60 s. After the reaction was completed, the mixture was cooled to obtain a powdered high-entropy carbide composite material with friction-induced self-lubricating function.

[0049] The obtained composite material was scanned by electron microscopy, and the results are as follows: Figure 3 As shown. By Figure 3 As can be seen, a continuous and uniform lubricating film was formed. Energy dispersive spectroscopy analysis confirmed that the lubricating film is rich in carbon elements, indicating that the single-walled carbon nanotube-derived lubricating phase plays a good lubricating role.

Claims

1. A high-entropy carbide composite material with friction-induced self-lubricating function, characterized in that: The composite material consists of a high-entropy carbide matrix and a carbon nanotube-derived lubricating phase; the high-entropy carbide matrix has the chemical formula (A1A2A3A4A5)C and has a face-centered cubic crystal structure, wherein A1, A2, A3, A4, and A5 are any five elements selected from W, Zr, Nb, Hf, Ta, Ti, and Mo, and the molar ratio of A1, A2, A3, A4, A5 to C is 1:1:1:1:1:

5.

2. The high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 1, characterized in that: The mass ratio of the carbon nanotube-derived lubricating phase to the high-entropy carbide matrix is ​​0.01~0.15:

1.

3. The high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 1, characterized in that: The coefficient of friction of the composite material is 0.1 to 0.45 in the temperature range of room temperature to 1000°C.

4. A method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in any one of claims 1 to 3, characterized in that: First, carbon nanotubes are used as the carbon source, and five metal oxides selected from WO3, Nb2O5, HfO2, ZrO2, Ta2O5, TiO2, and MoO3 are used as raw materials. The metal oxides are weighed according to the equimolar ratio of the metal elements, and the carbon nanotubes are weighed according to the molar ratio of carbon to each metal element of 5:

1. Then, the metal oxides and carbon nanotubes are mixed and placed in a high-energy ball mill for wet ball milling to obtain a mixed slurry. After drying, the mixed slurry is used to obtain a composite precursor powder. Finally, the composite precursor powder is placed in a Joule heating rapid heating device and subjected to a Joule heating rapid carbothermic reduction reaction under a protective atmosphere. After the reaction is completed and cooled, a powdered high-entropy carbide composite material with friction-induced self-lubricating function is obtained.

5. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The purity of the metal oxides is not less than 99.95%, and the particle size is not less than 100 mesh.

6. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The carbon nanotubes are multi-walled or single-walled carbon nanotubes with a purity of not less than 95%, a diameter of 5~50nm, and a length of 1~20μm.

7. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The ball milling conditions are as follows: rotation speed of 200~400 rpm, ball-to-material mass ratio of 5:1~15:1, ball milling time of 5~15 h, solvent of anhydrous ethanol, and mass ratio of anhydrous ethanol to raw material of (1~3):

1.

8. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The drying conditions refer to a temperature of 60~85℃ and a time of 12~24h.

9. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The Joule heating rapid heating device is a Joule heating reactor, with argon or nitrogen as the protective atmosphere and a gas flow rate of 0.1~1L / min; the heating rate is 100~600℃ / s, the heating temperature is 2000~2300℃, and the holding time is 30~180s.

10. The method for preparing a high-entropy carbide composite material with friction-induced self-lubricating function as described in claim 4, characterized in that: The powdered high-entropy carbide composite material with friction-induced self-lubricating function is formed into a bulk material by spark plasma sintering or hot pressing sintering. The sintering temperature is 1800~2000℃, the pressure is 30~50MPa, the holding time is 5~15min, and the relative density after sintering is not less than 98%, and the Vickers hardness is not less than 17GPa.